The Influence of Dynamic Capabilities on Business Performance Through Business Model Innovation Among MSMEs in Surabaya - Putra, I Putu Agus Ferdy Artama; Siahainenia, Johan Pratama; Efrata, Tommy Christian (Jurnal Entrepreneur dan Entrepreneurship, 2025)
This study aims to analyze how dynamic capabilities (sensing, seizing, and transforming) influence the performance of MSMEs in Surabaya, with business model innovation (BMI) as a mediating variable. This quantitative study method used a causal design using PLS-SEM to survey data from 120 MSME decision-makers across diverse sectors in Surabaya. The results show that dynamic capabilities positively and significantly affect MSME performance, both directly and indirectly through BMI as a partial mediator. The capability set of sensing, seizing, and transforming fosters adaptive business model innovations that respond to market demands. BMI contributes to efficiency, competitiveness, and sales growth, strengthening sustainable performance. These findings underscore the need for targeted training, mentoring, and access to technology and resources to enhance MSME innovation and adaptability amid ongoing market challenges.